Perilaku Konsumsi Mahasiswa Dalam Memanfaatkan Dompet Digital: Studi Kasus Mahasiswa/i UINSU Medan - Auliya Ahmad Suhardi; Saparuddin Siregar; Budi Dharma (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The advancement of time and technology that continues to develop brings enormous changes to various sectors of life today. This change is the presence of new innovations in digital-based financial and payment systems, namely the presence of e-wallets. The purpose of this study is to determine the consumption behavior of students in utilizing digital wallets, whether using a digital wallet makes them consumptive or can plan their finances in the future. This research was conducted using a descriptive qualitative method. The research results show that the use of digital wallets has an influence on student consumptive behavior. This can be seen from the consumption behavior of students in utilizing digital wallets. where students use digital wallets to fulfill all their needs, be it shopping online, paying electricity bills, credit, data, then ordering online transportation, ordering food and drinks and so on. Keyword : consumption behavior, digital wallet, and students